A new species of Gastropteridae (Gastropoda, Opisthobranchia, Cephalaspidea) from tropical Northeast Australia - Klussmann-Kolb, Annette; Klussmann, Alexander (Zootaxa, 2003)
A new species of the family Gastropteridae from tropical Australia is described. The main focus of the description is the external morphology, the radula morphology and the histology of all organ systems. Siphopteron leah sp. nov. is a small species with a bright yellow body colour and red lines along the siphonal crest, the parapodia, across the visceral hump and at the flagellum. The species is characterised by the presence of glandular cells along the inner side of the large parapodia, by two large spines on the penial bulb, by a three parted prostate and by a muscular pocket at the vagina. The inner lateral teeth of the radula are very distinct bearing a long curved cusp and two small stout denticles. This is the first detailed histological description of all organ systems in Siphopteron providing new insights into the anatomical structure and functional biology of these animals.